Deradicalization of religion through pluralism education methods in Islamic religious education in Bali, Indonesia - Saihu,; Ahmad Zain Sarnoto, (Technium Social Sciences Journal, 2020)
This paper discusses Islamic religious education activities with the color of pluralism in two formal institutions in Jembrana-Bali. Writing that focuses on methods of tracing learning used in learning Islamic Religious Education subjects as a learning tool to facilitate interaction between students who are Hindu and Muslim, making it a focus on peaceful practices in the educational environment. Data sources were obtained through unstructured observations and interviews during November 2018 to March 2019. The writing used the theory of peace education proposed by John Dewey (1859-1952). Writing that discusses the learning process of Islam with the color of pluralism can shape the character of students, both Hinduism and Islam to be humanist, tolerant, and inclusive. This paper also refutes to shape the character and character of students in Jembrana and also to foster-develop understanding, develop methods of contribution, enrichment, and decision-making and social action proposed by Allison Cumming-McCann. Thus, the construct of individual character is built so that the interaction models of Hindu and Islamic students interaction in Public Secondary School No. 4 Negara and Public Senior High School No. 1 Negara are all in the Jembrana Regency, the process of finding results, complementation, and sublimation. Through the Contribution learning method, which aims to invite students to deepen the beliefs (religions) they embrace and can participate in understanding and appreciating different cultures and religions from them, Through the Enrichment Learning method, which aims to Enrich the curriculum with literature from or different communities culture, ethnicity, and religion, are the directions and objectives of the enrichment method, and through learning methods of decision making and social action aimed at not only requiring students to understand social issues, but also doing something important related to the issues This, can minimize conflicts in the name of ethnicity, religion, race, and between groups, in the two educational institutions.